Surgical Stabilisation of a Coxofemoral Luxation in a Northern Goshawk (Accipter gentilis) with Transarticular Pinning - Marko Legler; Vanessa Guddorf; Michael Fehr (Veterinary Sciences, 2023)
A 3-year-old male northern goshawk (Accipiter gentilis) used in falconry for hunting was diagnosed with a craniodorsal coxofemoral luxation of the left leg after an unsuccessful hunting flight. Closed reduction in the dislocation was unsuccessful and the hip joint reluxed again with slight abduction of the limb. An open surgical reduction with a transarticular stabilization using a normogradely inserted Kirschner wire was performed. The implant was removed surgically after five weeks. After about seven weeks, the owner saw no abnormalities in the loading of the limbs, and the goshawk was successfully used for hunting after nine months in the next hunting season.